Analisa Kesehatan Fiskal di Provinsi Riau Periode 2019 – 2021 - Hamsina Mukaddas; Mohamad Saefudin; Mila Puspitasari; Kumba Digdowiseiso (LPPM Institut Nasional Laa Roiba Bogor, 2023)
The condition of regional fiscal health is a condition for implementing regional autonomy and fiscal decentralization. This study took samples of districts/cities in Riau Province in the period 2019 - 2021 to be analyzed using the Fiscal Health Index. The results of the analysis will be able to describe the condition of the fiscal health of each Regency/City in the Riau Province area before and during the Covid-19 pandemic. The research method used is a quantitative descriptive study and determines all districts/cities as the unit of analysis. The measurement model used refers to the Regulation of the Minister of Home Affairs of the Republic of Indonesia Number 19 of 2020 concerning Measurement of the Regional Financial Management Index, but only focuses on 3 (three) indicators from the dimensions of regional financial conditions. The three indicators are financial independence, financial flexibility, and service solvency. The results of this study can be concluded that of the 12 districts/cities in Riau Province are included in the low category, both in financial independence, financial flexibility and service solvency. This condition may affect their ability to implement decentralization and regional autonomy. Of the 12 Regencies/Cities in Riau Province that have the highest Fiscal Health Index in a row in 2019-2021 are Bengkalis and Kepaluauan Meranti Regencies, while those with the lowest Fiscal Health Index are Indragiri Hulu and Indragiri Hilir Regencies. This comparison is only in the scope of Regencies/Cities in Riau Province. Keywords: Regional Fiscal Health, Fiscal Decentralization, Financial Independence, Financial Flexibility, Service Solvability